2015
DOI: 10.5694/mja14.01628
|View full text |Cite
|
Sign up to set email alerts
|

Recall of anti‐tobacco advertising and information, warning labels and news stories in a national sample of Aboriginal and Torres Strait Islander smokers

Abstract: Objectives: To describe recall of anti‐tobacco advertising (mainstream and targeted), pack warning labels, and news stories among a national sample of Aboriginal and Torres Strait Islander smokers, and to assess the association of these messages with attitudes that support quitting, including wanting to quit. Design, setting and participants: A quota sampling design was used to recruit participants from communities served by 34 Aboriginal community‐controlled health services and one community in the Torres Str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 42 publications
3
18
1
Order By: Relevance
“…In general, targeted messages are indicated where beliefs and sources of motivation differ from those in the general population 25 . Elsewhere in this supplement, we report that beliefs about harm to others appear particularly motivating, 26 and that smokers who recalled more targeted or local targeted advertising were more likely to hold these beliefs 27 …”
Section: Discussionsupporting
confidence: 92%
“…In general, targeted messages are indicated where beliefs and sources of motivation differ from those in the general population 25 . Elsewhere in this supplement, we report that beliefs about harm to others appear particularly motivating, 26 and that smokers who recalled more targeted or local targeted advertising were more likely to hold these beliefs 27 …”
Section: Discussionsupporting
confidence: 92%
“…Elsewhere in this supplement, we show that more community members from sites with dedicated tobacco control resources had been advised to quit, 18 recalled noticing cigarette pack warning labels, 19 made quit attempts 20 and used stop‐smoking medicines 21 than those from sites without dedicated resources. However, there were no such significant differences for wanting to quit, 22 smoke‐free homes, 23 recalling advertising and news stories about smoking and quitting, 19 and personal attitudes towards smoking 24 …”
Section: Discussionmentioning
confidence: 88%
“…A national survey of 47 organisations, including primary health services, reported that community responses to messages targeting Indigenous Australians positively exceeded the organisations' expectations . Indigenous Australian smokers demonstrated good recall of anti-tobacco messages (Gould et al 2013a;Nicholson et al 2015a) and these messages were associated with intentions to quit smoking (Nicholson et al 2015b). This may be mediated by increased perceptions of the threat from smoking and reflective motivation (Nicholson et al 2015a).…”
Section: Effect Of Anti-tobacco Messages On Indigenous Pregnant Womenmentioning
confidence: 99%
“…Indigenous Australian smokers demonstrated good recall of anti-tobacco messages (Gould et al 2013a;Nicholson et al 2015a) and these messages were associated with intentions to quit smoking (Nicholson et al 2015b). This may be mediated by increased perceptions of the threat from smoking and reflective motivation (Nicholson et al 2015a). However, messages in isolation may not provide the opportunity, nor improve the capability of Indigenous smokers to quit, thus they should be supported by primary healthcare approaches.…”
Section: Effect Of Anti-tobacco Messages On Indigenous Pregnant Womenmentioning
confidence: 99%